Pengaruh Iklim Organisasi Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Kantor Pertanahan Kota Manado - Lagonah, Srijanti; Pio, Rianoe; Kaunang, Markus (JURNAL ILMIAH SOCIETY, 2016)
Organizational climate becomes very important because it is a place everyone to run its activities. It is undeniable that modern humans became a member of various organizations, all of which are intended to facilitate the achievement of objectives, interests and personal needs are becoming increasingly complex, especially physical needs. In an attempt to fulfill the needs of a physical nature, humans make a living through the efforts of an employee in something specific organizations, both within the government and among private. This study examines the influence of organizational climate and organizational culture on employee satisfaction, this research is located in the Office of Manado City, this is because the land office clerk in the city of Manado utilize organizational climate is not so disciplined and cause its impact on service to the community. This study uses a quantitative method used to test the theory.